Peningkatan Pengetahuan dan Keterampilan Mengaplikasikan Mosaik Keramik pada Furnitur Berbahan Kayu Bekas - Ariani, Ariani; Rizali, Awang Eka Novia; Dewanti, Asih Retno; Sumotarto, Untung (Universitas Islam Nahdlatul Ulama Jepara, 2023)
Ceramic mosaic is the art of arranging or combining ceramic pieces of certain colors and sizes to form an aesthetic pattern. Based on the evaluation results on the previous Community Service (PkM) implementation, it was found that the knowledge of the participants about mosaics, especially in terms of composition of shapes and colors, had not been fully mastered. Referring to this, this PkM activity aims to improve the knowledge and skills of participants in the Asem Baris area of gang V, RT 05, RW 05, in applying mosaics to furniture in the form of tables made of used wood. The method used in the preparation stage was to conduct experiments to obtain ceramics as the main raw material for mosaics, and to design a table with a disassembly system. At the stage of implementing PkM, the parsipatory and mentoring methods are carried out during the product development process. Â Â The results of this activity showed an increase in the participants' understanding and skills in applying the composition of shapes and colors in mosaics. This can be seen in the results of PkM in the form of mosaics with interesting abstract and regular patterns even though they only use a combination of two colors